2010
DOI: 10.2174/1874279301004010055
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Plant-Based Vaccines Against Diseases of Concern in Developing Countries

Abstract: Vaccination has been extensively used to prevent, eradicate and control infectious diseases. However, the development and implementation of new vaccines remains prohibitively expensive for middle and low income countries where such measures are surely needed most. The production of plant-based vaccines provides a promising alternative to create affordable biological products. In the past decade, a growing number of research groups worldwide have studied plant expression and parenteral or oral delivery of vacci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 84 publications
0
13
0
Order By: Relevance
“…This method requires very high cost and can harm the plant. [14,41] Nuclear transformation and chloroplast transformation can be done by biolistic method. These were the two types of antigen expression method [42].…”
Section: Direct Gene Delivery Methodsmentioning
confidence: 99%
“…This method requires very high cost and can harm the plant. [14,41] Nuclear transformation and chloroplast transformation can be done by biolistic method. These were the two types of antigen expression method [42].…”
Section: Direct Gene Delivery Methodsmentioning
confidence: 99%
“…For example, preclinical trials with influenza VLPs indicated their capacity to induce both humoral and cellular immune responses at low antigen doses. Several authors have reported antibody response to parenterally or orally administered plant‐derived antigens . As exogenous antigens, VLPs are taken up by professional antigen presenting cells (APCs), especially DCs, followed by antigen processing and presentation via MHC class II molecules, DC activation and maturation through up‐regulation of co‐stimulatory molecules and cytokine production, and stimulation of CD4+ T helper cells.…”
Section: Immunostimulation By Vlpsmentioning
confidence: 99%
“…Traditional vaccines are produced by applying fermentation technology in various cell culture systems. However, numerous limitation related to fermentation so that development of alternative systems for the production of vaccines is timely (Davoodi et al, 2009;Daniell et al, 2009;Gomez et al, 2010).…”
Section: Introductionmentioning
confidence: 99%